Covalent Organic Framework Nanosheets as Reactive Fillers To Fabricate Free-Standing Polyamide Membranes for Efficient Desalination - Khan, Niaz Ali; Yuan, Jinqiu; Wu, Hong; Huang, Tong; You, Xinda; Rahman, Ata Ur; Azad, Chandra S.; Olson, Mark. A.; Jiang, Zhongyi (ACS applied materials & interfaces, 2020)
Mixed matrix membranes (MMMs) have been more and more broadly utilized in membrane processes. Covalent organic frameworks (COFs) hold great promise as emergent nanofillers to fabricate high performance MMMs, however, only little studies about COFs materials in MMMs have been reported where COFs are all used as non-reactive fillers. Herein, we propose using -NH2 functionalized covalent organic framework nanosheets as reactive fillers (RCON) to fabricate MMMs. RCON altered the morphology and chemistry of MMMs by controlling the diffusion rate of piperazine (PIP) through hydrogen bonding prior to interfacial polymerization (IP) process and inducing the creation of ridges in the MMMs with subsequent increase in surface area (~ 24%). RCON were chemically cross-linked to the trimesoyl chloride (TMC) through amide bonding, subsequently elevating the hydrophilicity (~ 35%) and fouling resistance of MMMs. The presence of -NH2 groups elevated the RCON-PA compatibility, ensuring the high RCON loading of 5% in the MMMs without sacrificing salt rejection. Accordingly, the PA-RCON MMMs exhibited a flux of 46.5 L. m-2. h-1. bar-1, which is 6.8 times higher than that of the pristine PA membrane, while with a high rejection rate of 93.5% for Na2SO4.